Gastroparesis. Issue 6 (November 2015) - Tack, Jan; Carbone, Florencia; Rotondo, Alessandra
Abstract : Purpose of review: This review summarizes recent progress in the epidemiology, pathophysiology, and treatment of gastroparesis. Recent findings: The relationship between delayed gastric emptying and symptom pattern in gastroparesis and, related to it, its separation from functional dyspepsia remains an area of controversy and uncertainty. Pathophysiological studies have focused on the role of pyloric resistance and duodenal motility in generation of symptoms. In diabetic patients, glycemic control did not determine short-term changes in gastric emptying rate in type 2 diabetes, but poor glycemic control was a major risk factor for long-term development of gastroparesis in type 1 diabetes. At the cellular level, diabetic gastroparesis is characterized by loss of interstitial cells of Cajal (ICCs), and this is inversely correlated to the number of CD206+ macrophages, which are thought to have a protective effect on ICCs. Treatment trials have focused on dietary factors and a nasal spray formulation of metoclopramide. A meta-analysis of prokinetic studies found no association between symptom improvement and enhancement of gastric emptying in gastroparesis. Two controlled studies showed no benefit of tricyclic antidepressants (nortriptyline, amitriptyline) in idiopathic gastroparesis and functional dyspepsia with delayed emptying. Summary: The relationship between delay in gastric emptying, symptom pattern, and response to prokinetic therapy in gastroparesis is poor. In diabetes, gastroparesis is characterized by loss of ICCs, and this is inversely correlated to the number of CD206+ macrophages. Dietary interventions may help to alleviate symptoms. Tricyclic antidepressants do not provide symptomatic benefit to patients with idiopathic gastroparesis.